Application of saliva in COVID-19 diagnosis: Challenges and opportunities - Khan, Saif; Rafat, Dalia; Khan, Asad Ullah; Rahman, Syed Ziaur; Farhat, Nabeela (Bangladesh Journal of Medical Science, 2021)
Abstract not available Bangladesh Journal of Medical Science Vol.20(4) 2021 p.697-699